TeiR, a LuxR-Type transcription factor required for testosterone degradation in comamonas testosteroni (2004)
We have identified a new steroid-inducible gene (designated teiR [testosterone-inducible regulator]) in Comamonas testosteroni that is required for testosterone degradation. Nucleotide sequence analysis of teiR predicts a 391-amino-acid protein which shows homology between residues 327 and 380 (C-terminal domain) to the LuxR helix-turn-helix DNA binding domain and between residues 192 and 227 to the PAS sensor domain. This domain distribution resembles that described for TraR, a specific transcriptional regulator involved in quorum sensing in Agrobacterium tumefaciens. Analysis of the gene expression indicated that teiR is tightly controlled at the transcriptional level by the presence of testosterone in the culture medium. A teiR-disrupted mutant strain was completely unable to use testosterone as the sole carbon and energy source. In addition, the expression of several steroid-inducible genes was abolished in this mutant. Northern blot assays revealed that teiR is required for full expression of sip48–-HSD gene mRNA (encoding a steroid-inducible protein of 48 kDa and 3-17-hydroxysteroid dehydrogenase) and also of other steroid degradation genes, including those encoding 3-hydroxysteroid dehydrogenase, 5 –3-ketoisomerase, 3-oxo-steroid 1 -dehydrogenase, and 3-oxosteroid 4 -(5)-dehydrogenase enzymes. Moreover, when teiR was provided to the teiR-disrupted strain in trans, the transcription level of these genes was restored. These results indicate that TeiR positively regulates the transcription of genes involved in the initial enzymatic steps of steroid degradation in C. testosteroni.